2005
DOI: 10.1038/sj.emboj.7600770
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of HIV-1 integrase by p300 regulates viral integration

Abstract: Integration of HIV-1 into the human genome, which is catalyzed by the viral protein integrase (IN), preferentially occurs near transcriptionally active genes. Here we show that p300, a cellular acetyltransferase that regulates chromatin conformation through the acetylation of histones, also acetylates IN and controls its activity. We have found that p300 directly binds IN both in vitro and in the cells, as also specifically demonstrated by fluorescence resonance energy transfer technique analysis. This interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
158
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 34 publications
6
158
1
Order By: Relevance
“…The GST-IN expression vector was a generous gift from Dr. A. Cereseto (20). The histidine-tagged IN expression vector was a generous gift from Dr. A. Engelman and its expression and purification were performed essentially as described previously (21).…”
Section: Study Of In Vivo Protein-protein Interactions Using the Coimmentioning
confidence: 99%
See 1 more Smart Citation
“…The GST-IN expression vector was a generous gift from Dr. A. Cereseto (20). The histidine-tagged IN expression vector was a generous gift from Dr. A. Engelman and its expression and purification were performed essentially as described previously (21).…”
Section: Study Of In Vivo Protein-protein Interactions Using the Coimmentioning
confidence: 99%
“…Protein Expression and Purification-Expression and purification of histidine-tagged Rev-GFP and GST-IN conjugates were performed as previously described (19,20). The GST-IN expression vector was a generous gift from Dr. A. Cereseto (20).…”
Section: Study Of In Vivo Protein-protein Interactions Using the Coimmentioning
confidence: 99%
“…In addition to histones, HATs are able to acetylate other proteins including transcription factors. In vitro analysis using recombinant proteins showed that p300 can also acetylate three specific lysines (Lys264, Lys266, and Lys273) in the C-terminus of HIV-1 IN (Cereseto et al, 2005). Interestingly, the acetylation increased IN binding to LTR DNA its catalysis of the strand transfer reaction in vitro (Cereseto et al, 2005).…”
Section: Cellular Interactors Affecting On Integration Stepmentioning
confidence: 99%
“…Posttranslational modifications of HIV-1 IN by cellular enzymes have also been reported to be implicated in integration. p300, a histone acetyltransferase (HAT), was first identified as a cellular protein that directly binds to HIV-1 IN in vitro and in human cells (Cereseto et al, 2005). HATs are known as enzymes that catalyze the transfer of acetyl groups from acetyl coenzyme A (acetyl-CoA) to specific lysine residues within the N-terminal tails of nucleosomal histones.…”
Section: Cellular Interactors Affecting On Integration Stepmentioning
confidence: 99%
See 1 more Smart Citation